A Comprehensive Study on Peppermint Oil and Cinnamon Oil as Nanoemulsion: Preparation, Stability, Cytotoxicity, Antimicrobial, Antifungal, and Antioxidant Activity - Özakar, Emrah; Alparslan, Levent; Adıgüzel, M. C.; Torkay, Gülşah; Baran, Alper; Bal-Öztürk, Ayça; Sevinç-Özakar, Rukiye (Current Drug Delivery, 2024)
Background: Recent studies have shown that nanoemulsions prepared with essential oils have significant antimicrobial potential against multidrug-resistant pathogens due to increased chemical stability. Nanoemulsion also promotes controlled and sustained release, which increases their bioavailability and efficacy against multidrug-resistant bacteria. Objective: This study aimed to investigate the antimicrobial, antifungal, antioxidant, and cytotoxicity properties of cinnamon essential oil and peppermint essential oil as nanoemulsions compared to pure forms. For this purpose, analyses of the selected stable nanoemulsions were carried out. Method: The droplet sizes and zeta potentials of peppermint essential oil nanoemulsions and cinnamon essential oil nanoemulsions were found to be 154.6±1.42 nm and -17.1±0.68 mV and 200.3±4.71 nm and -20.0±0.81 mV, respectively. Although the amount of essential oil used in nanoemulsions was 25% w/w, antioxidant and antimicrobial activities were found to be more effective compared to pure essential oils. Results: In cytotoxicity studies on the 3T3 cell line, both essential oil nanoemulsions showed higher cell viability than pure essential oils. At the same time, cinnamon essential oil nanoemulsions exhibited a higher antioxidant property than peppermint essential oil nanoemulsions and showed superiority in the antimicrobial susceptibility test conducted against four bacteria and two fungi. Cell viability tests determined that cinnamon essential oil nanoemulsions showed considerably higher cell viability compared to pure cinnamon essential oil. Conclusion: These findings indicated that the prepared nanoemulsions in the current study might positively influence the dosing regimen and clinical outcomes of antibiotic therapy.
Keywords: antimicrobial